2017
DOI: 10.1212/wnl.0000000000003660
|View full text |Cite
|
Sign up to set email alerts
|

High-dose immunosuppressive therapy and autologous HCT for relapsing-remitting MS

Abstract: Objective:To evaluate the safety, efficacy, and durability of multiple sclerosis (MS) disease stabilization after high-dose immunosuppressive therapy (HDIT) and autologous hematopoietic cell transplantation (HCT).Methods:High-Dose Immunosuppression and Autologous Transplantation for Multiple Sclerosis (HALT-MS) is a phase II clinical trial of HDIT/HCT for patients with relapsing-remitting (RR) MS who experienced relapses with disability progression (Expanded Disability Status Scale [EDSS] 3.0–5.5) while on MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 37 publications
8
132
0
9
Order By: Relevance
“…For HALT-MS, 24 of 25 subjects mobilized successfully with G-CSF and prednisone; 1 individual required subsequent mobilization using cyclophosphamide [1,2]. For SCOT, of 34 subjects treated with G-CSF and prednisone for mobilization, 2 needed a second course of G-CSF and prednisone, whereas a third required cyclophosphamide to achieve successful mobilization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For HALT-MS, 24 of 25 subjects mobilized successfully with G-CSF and prednisone; 1 individual required subsequent mobilization using cyclophosphamide [1,2]. For SCOT, of 34 subjects treated with G-CSF and prednisone for mobilization, 2 needed a second course of G-CSF and prednisone, whereas a third required cyclophosphamide to achieve successful mobilization.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects were mobilized for PBSC collection using G-CSF and prednisone, for the HALT-MS and SCOT studies, as described [1,2,6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditioning regimens with the strongest traction within each intensity category are cyclophosphamide and ATG (low intensity), BEAM and ATG (intermediate intensity) and cyclophosphamide, busulfan and ATG (high intensity). In the absence of evidence from randomized comparisons, we endorse the preferential use of BEAM and ATG -the scheme that is specifically recommended for the treatment of MS in the EBMT guidelines 56 -by virtue of its extensive track record that indicates good safety and high efficacy 14,73 , and of the opportunity it provides for comparisons across data sets.…”
Section: [H3] Conditioning Regimenmentioning
confidence: 99%
“…6,7 Similar developments happened worldwide and there have been a large number of retrospective and prospective studies in a wide range of ADs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] More recently, randomized controlled trials have reported confirming proof of principle in several ADs. [28][29][30][31][32] Despite international guidelines and recommendations, the uptake of HSCT in AD has been highly variable, both geographically and in respect to type of AD.…”
Section: Introductionmentioning
confidence: 99%